Sludge dewaterability: The variation of extracellular polymeric substances during sludge conditioning with two natural organic conditioners. (1st December 2019) - Faye, Marie Christine Amie Sene; Zhang, Kai Kai; Peng, Sun; Zhang, Yanrong
Abstract: To assess the characteristics of Extracellular Polymeric Substances during natural organic conditioners for sludge treatment, Moringa oleifera (MO ) and chitosan (CTS) were used as conditioners. The findings of this study show that despite the high EPS content due to the fact that this component is not destroyed upon conditioning, sludge conditioned with MO and CTS displayed efficient and improved dewaterability. MO and CTS showed the same mechanism of action by protonation of the negatively charged EPS and reduction of electrostatic repulsions between sludge flocs, thus enhancing sludge filterability by neutralizing and settling. The effect of MO and CTS on EPS lies in their ability to neutralize EPS, settling them. MO and CTS neutralize and aggregate the EPS, hence improving sludge dewaterability. The results indicate that CTS can impact the EPS quantity and quality while MO impacts the EPS quality. Understanding the impact of MO and CTS on sludge EPS can help elucidate the mechanism of their dewaterability efficiency. Highlights: High EPS content was achieved during sludge conditioning. Positive correlation between EPS reduction and sludge dewaterability was observed. The effect of Moringa oleifera and Chitosan on EPS lies in their ability to neutralize EPS, settling them. The results indicate that chitosan can impact the EPS quantity and quality while Moringa oleifera impacts the EPS quality.